A Critical Dose of Doxorubicin Is Required to Alter the Gene Expression Profiles in MCF-7 Cells Acquiring Multidrug Resistance - Tsou, Shang-Hsun (PLoS One, 2015)
Cellular mechanisms of multidrug resistance (MDR) are related to ABC transporters, apoptosis, antioxidation, drug metabolism, DNA repair and cell proliferation. It remains unclear whether the process of resistance development is programmable. We aimed to study gene expression profiling circumstances in MCF-7 during MDR development. Eleven MCF-7 sublines with incremental doxorubicin resistance were established as a valued tool to study resistance progression. MDR marker P-gp was overexpressed only in cells termed MCF-7/ADR-1024 under the selection dose approaching 1024 nM. MCF-7/ADR-1024 and authentic MCF-7/ADR shared common features in cell morphology and DNA ploidy status. MCF-7/ADR-1024 and authentic MCF-7/ADR down regulated repair genes BRCA1/2 and wild type p53, apoptosis-related gene Bcl-2 and epithelial-mesenchymal transition (EMT) epithelial marker gene E-cadherin. While detoxifying enzymes glutathione-S transferase-π and protein kinase C-α were up-regulated. The genes involving in EMT mesenchymal formation were also overexpressed, including N-cadherin, vimentin and the E-cadherin transcription reppressors Slug, Twist and ZEB1/2. PI3K/AKT inhibitor wortmannin suppressed expression of Slug, Twist and mdr1. Mutant p53 with a deletion at codons 127-133 markedly appeared in MCF-7/ADR-1024 and authentic MCF-7/ADR as well. In addition, MCF-7/ADR-1024 cells exerted CSC-like cell surface marker CD44 high/CD24 low and form mammospheres. Overall, results suggest that resistance marker P-gp arises owing to turn on/off or mutation of the genes involved in DNA repair, apoptosis, detoxifying enzymes, EMT and ABC transporters at a turning point (1.024 μM doxorubicin challenge). Behind this point, no obvious alterations were found in most tested genes. Selection for CSC-like cells under this dose may importantly attribute to propagation of the population presenting invasive properties and drug resistance. We thereby suggest two models in the induction of drug resistance. Model 1: Selection for CSC-like cells. Model 2: Mutations for gain-of resistance. Either model 1 or model 2 requires doxorubicin dose approaching 1 μM to alter gene regulation.